Analisis of the process for traditional general contracting in Sarawak Malaysia - Tsen, S.F (University Malaysia Sarawak, UNIMAS., 2006)
This project investigate on the problems that could occur in every stage of the tender process and to see if there are rooms for improvement. The improvement is necessary so as to optimize the tender process to meet the objective of a construction contract.